Regional Differentiation in the Development of French Towns — Quantitative Analysis - Sławomir Dorocki (Barometr Regionalny, 2012)
The 20th and 21st centuries are the periods of urbanization. In 2008, for the first time the world’s urban population exceeded 50%. This process is driven mainly by technological, economic and social changes. In the case of Europe, “metropolitan Europe” has already become a commonly used name. However, the question arises as to whether the processes of urbanization take place with the same intensity throughout Europe and if there are any regional differences in these changes. This paper attempts to present regional differences in the development of cities in France. As an indicator of development the changes of city population have been adopted. The analysis was based on the number of urban population in France in the years 1965–2007. The analysis of these changes was carried out in relation to various administrative units: regions, departments, units and urban agglomerations (unité urbaine). After analyzing the changes of the degree of urbanization of regions an attempt was made to create a model of urban development in various regions of France and, on this basis, forecast their future growth. Finally, selected indicators of socio-economic changes have been compared with the rate of urban population changes. This has been aimed at verifying the influence of individual factors on contemporary processes of urbanization.